JURIDICAL ANALYSIS OF THE INVESTIGATOR'S AUTHORITY IN THE DETENTION OF CRIMINAL SUSPECTS TO REALIZE LEGAL CERTAINTY - Fitra Azli; Dahlan Dahlan; Ramlan Ramlan; Erniyanti Erniyanti; Fadlan Fadlan (International Journal Labs, 2022)
Background: Indonesia is a country of law and is not based on mere power, all state power is governed by law. Criminal law is the rule of conducting a public order by prohibiting what is contrary to the law and giving a message to those who violate the prohibition. To enforce material criminal law requires formal law (criminal procedural law). The handling of criminal cases in principle comes from investigation, investigation, prosecution, and ends with a judge's ruling. At the investigation stage, the investigator is authorized to detain suspects whose implementation is regulated in the Criminal Procedure Code to realize legal certainty Objective: The purpose of this study is to juridically analyze the authority of investigators in the detention of criminal suspects to realize legal certainty. Methods: The author uses normative and empirical legal research methods. Normative legal research by conducting studies through literature studies and secondary data. Empirical research using primary data, namely data obtained from the results of direct research conducted through interviews. Results: The results of the research on the authority of the investigator in detaining suspects of criminal acts regulated by article 20 paragraph (1) of the Criminal Procedure Code. Influencing factors include fearing that the suspect will flee, tamper with/remove evidence and/or repeat criminal acts. Other considerations of the suspect are the target of the operation, the suspect where he lives is far away is unclear, the suspect committed a criminal act that is the attention of the leadership, the case that occurred has been reported by the mass media and has received widespread attention from the public. The legal consequence faced by investigators in exercising the authority to detain suspects is a pretrial lawsuit. Conslusion: The legal consequence of the actions of the Police investigator in exercising his authority over the detention of suspects, that in carrying out detention, they must still pay attention to the rights of suspects, and suspects can apply for pretrial